Determination of the serum antibody level of different age groups of broiler chicken against Infectious Bursal Disease (IBD) (International Journal of Natural Sciences, 2016)
A study on Infectious Bursal Disease (IBD) was conducted on broiler chicks (N=200+70) of strains: Cobb-500 and Hubbard classic at Laxmipur district of Bangladesh. The blood sample were collected at day old chicks (1st day), pre-vaccinated flocks (11th day) and post-vaccinated flocks (26th day), to measure the antibody titer by indirect ELISA method. Maternal derived antibody (MDA) mean titer of day old chicks (N=40) were found 9621.65 ± 780.78 and 4232.60 ± 301.66 for Cobb-500 and Hubbard classic respectively. MDA mean titer was measured at day eleven chicken (N=60) before vaccination and found 1963.00 ± 143 and 984.16 ± 126.4037 respectively. Of these two titers; Cobb-500 strain was found to be protective (>1000) where Hubbard classic was below protective (